1990
DOI: 10.1111/myc.1990.33.7-8.405
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on the ultrastructure of Histoplasma capsulatum during the mycelium‐yeast transition

Abstract: The ultrastructural morphology of the early phases of mycelium-yeast transition in Histoplasma capsulatum after a temperature shift from 25 degrees C to only 34 degrees C is described. Under this condition of lower temperature oxidative phosphorylation is not completely uncoupled and maximum production of heat shock proteins (hsp) occurs. 24 h after temperature shift more than 90% of the cells still appear vital. Alterations in the organization of the mitochondrial cristae are the only ultrastructural changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This is accompanied by an increase in the number of interactions with proteins involved in protein and carbohydrate metabolism, specifically at the cell wall level. These increased interactions might occur in the stress recovery phase, in response to the uncoupling of oxidative phosphorylation [66] and a decline in intracellular ATP levels [67]. Additionally, it has been shown that respiration is coupled in the yeast phase at 37°C, and this change results in cellular adaptation to higher temperatures [65].…”
Section: Discussionmentioning
confidence: 99%
“…This is accompanied by an increase in the number of interactions with proteins involved in protein and carbohydrate metabolism, specifically at the cell wall level. These increased interactions might occur in the stress recovery phase, in response to the uncoupling of oxidative phosphorylation [66] and a decline in intracellular ATP levels [67]. Additionally, it has been shown that respiration is coupled in the yeast phase at 37°C, and this change results in cellular adaptation to higher temperatures [65].…”
Section: Discussionmentioning
confidence: 99%